Caracterización de la situación idiomática de los pueblos indígenas de Costa Rica y su influencia en su educación - Vásquez Carvajal, Ana Cecilia (2008)
This essay shows the reality of Costa Rican indigenous groups in terms of the mastery and promotion of their original tongue and the way this has been taken into account in the design of the curricula of their schools. In general, it is discussed that the educational process is developed disengaged of the idiomatic and cultural reality of these groups, even tough government efforts have been made in this direction. As a result of this educational deficiency, a cultural decline is generated that might end up with the loss of native languages.